(untitled) (Journal of Medical & Health Sciences Review, 2025)
Preventing postoperative pulmonary regurgitation (PR) is critical for favorable outcomes following Tetralogy of Fallot (TOF) repair. The right atrial appendage (RAA) valve for right ventricular outflow tract (RVOT) reconstruction is a novel technique that offers a promising alternative when the native pulmonary valve cannot be preserved. This cross-sectional study evaluated the use of the RAA valve in 102 consecutive patients who underwent TOF repair at our institution between December 2023 and May 2025. The mean age was 6.5 years (range: 4 months–32 years). There were four deaths, none attributed to RAA valve use. Early postoperative echocardiography revealed trivial or no PR in 61 patients, mild PR in 33, and moderate PR in 8, with no severe PR. None developed significant RVOT obstruction. The mean tricuspid annular plane systolic excursion (TAPSE) was 14 mm. The average cardiopulmonary bypass and aortic cross-clamp times were 98 and 78 minutes, respectively. Postoperative complications included two re-openings for bleeding or tamponade, three strokes, six reintubations, five cases of renal dysfunction (one requiring dialysis), one heart block not requiring pacemaker, and one superficial wound infection. Overall, RAA valve reconstruction appears feasible, safe, and effective in reducing early PR, with encouraging short-term outcomes. Longer follow-up is warranted to assess durability and its role in delaying pulmonary valve replacement.